Clinical and functional state of the retina after adequately performed laser coagulation of peripheral vitreochorioretinal dystrophies - V. V. Neroev; G. Yu. Zakharova; T. D. Okhotsimskaya; I. V. Tsapenko; M. V. Zueva; M. A. Arakelyan; B. M. Magamadov (Российский офтальмологический журнал, 2022)
Перенести в английский вариант   Purpose.  To assess the effect of adequate laser coagulation (LC) of peripheral vitreochorioretinal dystrophy (PVCRD) on the clinical and functional state of the retina and the microcirculation of the macular region.     Material and methods.  Ganzfeld electroretinogram (ERG), multifocal ERG (mfERG), and optical coherent tomography with a function of angiography (OCTA) were performed for the retina of 22 patients (37 eyes), aged 20 to 62, who had been given an adequate volume of LC to treat dangerous types of PVCRD. The tests took place before LC and 1, 3, 6, 9, 12 months after it. To analyze the results, two groups were formed: (1) 27 eyes with LC volume of less than 200 coagulates and (2) 10 eyes with LC volume of more than 200 coagulates.   Results.  After LC, we observed a moderate decrease in the amplitudes of scotopic ERGs and the a-wavepeak latency lengthening in the maximal ERG. In the 2 ndsubgroup, the amplitude of the second wave of oscillatory potentials (OP2) and the OP index decreased more significantly than in the 1st, subgroup (by 17 and 21 % from the initial values, respectively, p<0.05). The cone and flicker ERGs in the 1st subgroup did not change, while in the 2nd subgroup the amplitude showed a stable decrease by 10 to 20 % as compared to the data before LC. As shown by mfERG, in the 2nd subgroup the functional activity of the macular region was moderately and reversibly declining. OCTA showed a general decrease in blood flow density (by 6.6% against the initial data) after LC, which reached the minimum 6 months after the intervention, with subsequent recovery in another 6 months. The recovery of blood flow density was complete in the 1st subgroup and partial in the 2 nd subgroup.   Conclusion.  LC of PVCRD in an adequate volume leads to a moderate general decrease in retinal activity with the restoration to the initial amplitudes of scotopic and photopic ERGs, and mfERG within 6 to 12 months. OCTA also showed that LC conducted in an adequate volume does not significantly impair the microcirculation in the fovea zone. A moderate depression of blood flow was more pronounced in the subgroup with the higher number of coagulates.